Association of good oncological response to therapy with the development of rheumatic immune‐related adverse events following PD‐1 inhibitor therapy. (22nd November 2018) - Liew, David F. L.; Leung, Jessica L. Y.; Liu, Bonnia; Cebon, Jonathan; Frauman, Albert G.; Buchanan, Russell R. C.
Abstract: Aim: To investigate whether any patient or treatment characteristics are associated with the development of rheumatic immune‐related adverse events (irAEs) following programmed cell death protein 1 (PD‐1) inhibitor therapy for cancer. Method: This was a retrospective chart review of all patients who were dispensed nivolumab or pembrolizumab at a single center before 1 January, 2017, with follow‐up until 1 July, 2017. Patients with any diagnosis of a non‐cutaneous irAE were identified, regardless of severity, and rheumatic irAEs were characterized. Results: Of 244 episodes of therapy, a non‐cutaneous irAE occurred in 72 (29.5%). Rheumatic irAEs were diagnosed in 19 episodes of therapy (7.8%), with 12 de novo diagnoses (5.1% of episodes without a pre‐existing autoimmune rheumatic disease) and 7 exacerbations of existing disease. Review by a rheumatologist occurred in only 11 of these. Rheumatic irAEs were more common in patients with a good oncological response to therapy (relative risk [RR] 11.16), those being treated for melanoma (RR 2.94) and those who developed another non‐cutaneous irAE (RR 2.64). Conclusion: Rheumatic irAEs are relatively common with PD‐1 inhibitor therapy, and appear to be associated with a good oncological response to therapy. Many rheumatic irAEs were not referred to rheumatological services. Prospective systematic investigation would be of benefit to explore these characteristics.